We start with an arbitrary 3-CNF formula $f$. We take as an example:
$$ f = (\neg x_1 \vee \neg x_2 \vee x_3) \wedge (\neg x_1 \vee x_2 \vee x_4) \wedge (x_1 \vee x_3 \vee x_4) $$
Now we define for every negated literal $\neg x_k \Leftrightarrow x_{k + n}$ with $n$ the number of literals in $f$. We then replace all negated literals with their non-negated counterparts, which we can do in linear time. For the example we then get:
$$ f = (x_5 \vee x_6 \vee x_3) \wedge (x_5 \vee x_2 \vee x_4) \wedge (x_1 \vee x_3 \vee x_4) $$
And we get $f$ in a beautiful form. Now we have the constraints $\neg x_k \Leftrightarrow x_{k + n}$ or equivalently $(x_k \vee x_{k + n}) \wedge (\neg x_k \vee \neg x_{k + n})$. Adding these constraints to $f$ we get:
$$g = f \wedge (x_1 \vee x_5) \wedge (\neg x_1 \vee \neg x_5) \wedge (x_2 \vee x_6) \wedge (\neg x_2 \vee \neg x_6)$$
The constraints can be added in linear time. Now we have that $f$ has been made into a beautiful formula and the additional constraints can also be made beautiful and so $g$ is beautiful. And so we have started from an arbitrary 3-CNF formula and reduced it to an equivalent beautiful formula in polynomial time. This concludes the proof.